Unlocking the Potential of the Bangsamoro People through the Alternative Learning System - World Bank (World Bank, Washington, DC, 2019)
In 2018, after decades of conflicts, peace negotiations finally concluded with the creation of the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), recently approved through the 2019 Bangsamoro autonomy plebiscite, which is envisioned to have greater autonomy, more resources, and larger territory than its predecessor. BARMM has faced serious challenges in both access and quality of basic education even while the Philippines as a whole has made remarkable progress in the basic education reform over past decades. In BARMM, only 1 out of every 10 students who began primary education completes junior high school (JHS) on time. Out-of-school youth and adults (OSYA) have thus accumulated over the generations. The share of OSYA in BARMM is double the national average. The figures point to a crisis in the delivery of basic education in the BARMM area – a crisis which needs to be addressed as a first priority to keep children in school and to provide better quality education to them. Complementary to the efforts in provide quality education for Filipino children, the Alternative Learning System (ALS) has been operated by the Department of Education (DepEd) offering second-chance learning programs for the past few decades throughout the country for OSYA who have limited skills and bleak employment prospects. The World Bank has undertaken a series of evaluations of ALS with the DepEd since 2013. The findings show significant and positive impacts on labor market outcomes among ALS learners who could pass the accreditation and equivalency (A&E) exam. The previous evaluations of ALS have not to date covered the BARMM area. This study fills that gap and aims to provide the new BARMM government essential evidence based on new data for designing and undertaking reform interventions to improve the program delivery for its beneficiaries.